Self-Confidence and Successful Interscholastic Athletic Coaching at the High School Level - Berry, Tony (Southwest Baptist University, 2014)
The researcher sought to increase understanding into one characteristic of successful leadership of interscholastic high school coaches in Missouri. Generally coaches are trained in a similar methodology as to the construct of teaching, but consistently, there are outliers in the field of coaching that surpass other coaches in success as measured by wins and losses. The premise of the researcher was self-confidence of the head coach has a causal effect on a sports team’s ability to win championships, primarily state championships as defined by the Missouri State High School Activities Association (MSHSAA). A holistic view of the self-confidence of coaches in Missouri public schools who have won multiple state championships was sought by inclusion of all multiple championship winning coaches regardless of age, gender, or sport. The criteria for inclusion in the two groups studied and classified was by having won two or more state championships or by not having won two or more state championships. The researcher requested an email list of member schools from MSHSAA. From this list an email was sent to all public school athletic directors, asking them to have their head coaches complete and submit the questionnaire. From this email, 289 participants completed the questionnaire. The instrument used for this study was the Coaching Efficacy Scale developed by Feltz (1999). This instrument was a twenty-four question survey measuring the confidence coaches have while leading their teams. The questionnaire asked questions involving four categories of confidence. The coach’s ability to motivate the players, teach technique, use of strategy, and building character. The statistical analysis applied to the groups included a MANOVA for the four groups of questions and a t-test for each question. The researcher noted significant differences in three categories for each group, and for twenty of the twenty-four questions. The categories that revealed a significant difference were in the areas of confidence, technique and strategy. Confidence in the ability to build character did not show a significant difference between the two groups.